2020
DOI: 10.1038/s41598-020-77656-0
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology analysis of osteogenic differentiation behavior by canine mesenchymal stem cells derived from bone marrow and dental pulp

Abstract: Utilization of canine mesenchymal stem cells (cMSCs) for regenerating incorrigible bone diseases has been introduced. However, cMSCs harvested from different sources showed distinct osteogenicity. To clarify this, comparative proteomics-based systems biology analysis was used to analyze osteogenic differentiation behavior by cMSCs harvested from bone marrow and dental pulp. The results illustrated that canine dental pulp stem cells (cDPSCs) contained superior osteogenicity comparing with canine bone marrow-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 81 publications
3
31
0
Order By: Relevance
“…Our flow cytometry assay was able to characterize canine BM-MSCs as CD90 + , CD44 + , CD34 − , CD45 − , e MHC II − . Herein, canine BM-MSCs exhibited a comparable in vitro profile as described in previous studies 39 , 43 46 .…”
Section: Discussionsupporting
confidence: 65%
“…Our flow cytometry assay was able to characterize canine BM-MSCs as CD90 + , CD44 + , CD34 − , CD45 − , e MHC II − . Herein, canine BM-MSCs exhibited a comparable in vitro profile as described in previous studies 39 , 43 46 .…”
Section: Discussionsupporting
confidence: 65%
“…Morphological features are important in defining MSCs as they present as fibroblast-like cells. It has been reported that this feature is possessed by BM-MSCs derived from human [ 45 ], canine [ 46 47 ], feline [ 19 ], rat [ 48 ], and murine [ 49 ] sources. To the best of our knowledge, murine MSCs are smaller than human, canine, and feline cells.…”
Section: Stemness Characteristics Of Bm-mscsmentioning
confidence: 99%
“…In addition, Rex1 has been considered a pluripotency marker [ 51 ]. It has been reported that pluripotency TFs are expressed in all BM-MSCs derived from human [ 51 52 53 ], canine [ 46 54 ], rat [ 55 ], and murine [ 56 ] sources. Moreover, Ki67 is a proliferation marker, based on its reported expression in BM-MSCs derived from rat [ 55 ] and canine [ 46 ] but not human [ 57 ] sources.…”
Section: Stemness Characteristics Of Bm-mscsmentioning
confidence: 99%
“…Their characteristics were similar to those described in previous reports, including fibroblast-like structures, mRNA expressions related to stemness and proliferation, and MSC-related surface marker expression, along with the multilineage differentiation potential toward osteogenic, chondrogenic, and adipogenic lineages 16 – 18 , 31 34 . In this study, we employed the flow cytochemistry analysis on the expression of representative MSC-related and hematopoietic surface markers (Cd73, Cd90, and Cd45) according to our recent publication 35 . The expression of Cd73 in both MSCs was relatively low, as mentioned in a previous report 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent publication from our team regarding bone tissue engineering also showed the distinct osteogenic differentiation potential by cBM-MSCs and canine dental pulp stem cells (cDPSCs) in vitro. To dissect the underlying mechanisms, proteomics-based systems biology analysis was applied, and it suggested that both cells required different signaling pathways and underlying mechanisms for regulating their osteogenic paths 35 .…”
Section: Discussionmentioning
confidence: 99%